Development of Cultural Tourism in Macau through the Visual and Performing Arts - Tique, Ana Teresa Leal (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The effect of managers' cultural and educational background on management style: a study of middle level managers in Macao - Tam, Hoi Iong (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Towards an architecture center in Macau: vision and feasibility - Simões, Ana Filipa Brito da Cruz Rodrigues (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring the role of vocational education in promoting the diversification of Macao's industry: a study of the cultural and creative industries - Ngai, Hio Peng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Employee Motivation in Social Enterprise: The Case of Caritas Elderly Care Services in Macau - Mui, Un Kei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Corporate Social Resopnsibility Practices in Macau - Marcelo, Nicole Chantal Clemente (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Financial Valuation of Walmart Inc - Lestro, Gonçalo Nuno das Neves Arrojado (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Consumer purchase intention towards floral products: a study based on the five consumption values - Lei, Si Nga (University of Saint Joseph, 2023)
This dissertation focused on the consumers’ consumption behavior in Macau flower retailers. It revealed what factors affect consumers’ choice of flower shops during purchase. Also, what contributes to the customers’ loyalty towards a flower retailer by having interviews with the female target groups aged between 20 to 50 who work in the office. This study is important to the flower business owner because the result can allow them to understand the thoughts and feelings of their consumer. By interviewing 11 heavy users of floral products with 16 questions based on the five consumption values, we can communicate with the consumers directly and learn the reasons behind their purchasing behavior. Questions have been divided into 5 consumption values according to the previous research by (Sheth, Newman, & Gros, 1991), including functional, conditional, social, emotional, and epistemic values. The research has collected data on how and at what level these values may affect consumer consumption choices individually. The finding part analyzed the reason why those values affect consumers’ choices. Most of the interviewees stated that service is the most important compared to quality because the owner should be enthusiastic to provide product information and understand the consumer very well to impress and retain them with good personal service
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; consumption behavior; floral product; purchase intention

A Study of Social Enterprises in Macau: The Contributing Factors to The Development of Hybrid Social Enterprises - Hau, Pak Kei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Comparative study: The Human rights situation in China, the USA and Europe - Chu, Pok Tou; Lao-Phillips, Jenny Oliveros (University of Saint Joseph, 2023)
This thesis mainly discusses and compares the human rights situation and the problems in China, the USA and the UK. Also, the thesis will give the solution of how to make the world's human rights situation more fairly. Because we sometimes listen to these countries use cruel ways to suppress the opponents from the news. So I think this will be very suitable for understanding the current human rights situation, problems and movements in these countries. This thesis mainly uses the secondary data analysis method to collect and analyse the data. After analysing the data, three main issues affecting human rights were identified. These issues are race, religion, and network privacy. Other important factors still influence human rights, but this dissertation focused on the three issues identified. Finally, I will give two to three recommendations to practice human rights more fairly. Although the step will be very small, we can greatly improve the fair human rights in the future
Keywords: China; Europe; Human rights; Human rights situation; Thesis and Dissertations Master of Government Studies (MGS); USA; United Kingdom; University of Saint Joseph

How Does Employer Brand Affect Employer of Choice? A Case Study of Two Macau F&B Groups’ Employer Branding Comparisons - Chen, Zhi Yi (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The attractiveness of Taobao: why do people always come back despite negative feedback - Chan, Nga Man (University of Saint Joseph, 2023)
Online shopping in Macau has developed rapidly in recent years. And the success of Taobao is significantly hard to not notice. Its’ sales are breaking the record every year. However, there are a lot of negative comments towards Taobao. Various researches and data have shown that live-streaming is one of the biggest contributions towards Taobao’s sales and record breaking. This research aims to investigate deeply to understand how Taobao counters those issues and the role of live-streaming in relation to it. Based on a review of the literature in the relevant areas , qualitative methodology is adopted after thorough considerations. A small sample size of 10 were selected to conduct semi-structured in-depth interviews and the participants agreed to respond to answer the original interview questions and the follow-up questions. Analysis of the responses demonstrated e-customer service is the most influential variable towards repurchase intention. Live-streaming strategy can effectively and directly reduce constomer’s uncertainty of products and increase the efficiency of responsiveness. And product uncertainty and responsiveness speed are variables that impact purchase intention. The result demonstrated live-streaming's effectiveness in combating multiple negative aspects of Taobao and strengthening the positive aspects. On this basis, live-streaming is an impactful method to combat Taobao. In addition, e-service in terms of sufficiency of the staff’s communication skill have been found important towards customer’s satisfaction. A gap related to such an issue has been recommended in the further research recommendations along with other factors or sample groups, which are needed to explore deeply in the future
Keywords: Authenticity; Customer satisfaction; E- Service quality; Repurchase intention; Taobao; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Till Death Do (Not) Us Part: Elderlies’ Preparation on Wealth Transmission and the Effectiveness of Testaments in Macao - Chan, Hong Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Factors Influencing Disability Inclusion Practice in Social Media: A Case Study of MDA Service Centre for the Deaf - Chan Wai Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Study of management style in Canada - Ao, Ka Chon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The 50 Reasons for Voluntary Turnover: A Qualitative Exploration of Factors Contributing to Former Teacher Attrition in Macau - Ao, I. Leng (University of Saint Joseph, 2023)
Teacher turnover is a global issue that has not received much research attention in Macau despite studies indicating that teachers in the region experience high levels of stress and burnout. Given that private school teachers account for a significant proportion (88.6%) of the non-tertiary education system in Macau, this qualitative study focused on this specific group who voluntarily resigned from their positions. Through in-depth interviews with 13 former teachers from different kindergartens, primary, and secondary schools, the research identified 50 reasons categorized into 15 factors under three categories. Although schoolrelated factors account for the most, personal reasons were found to be the primary driver. The findings of the study highlight the complex nature of teacher turnover which can be attributed to both single and multiple factors, in both direct and indirect forms. The factors could also interplay in both unidirectional and mutual relationships. A conceptual framework for teacher turnover in Macau was developed to address the 15 contributing factors and the complex interplay of these factors. This study could fill the gap in the literature and serve as a valuable resource for policymakers and school leaders seeking to reduce teacher attrition rates in the region
Keywords: Macau; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; leavers; teacher turnover